2020
DOI: 10.37201/req/110.2020
|View full text |Cite
|
Sign up to set email alerts
|

High-dose trivalent influenza vaccine: safety and immunogenicity

Abstract: Adults aged 65 years or older suffer the most severe health effects of seasonal flu. Although the influenza vaccine is effective in preventing influenza virus infection and its complications, it is not as effective in the elderly due to age-associated immunosenescence phenomenon. Since 2009, a high-dose trivalent influenza vaccine has been approved in the United States for the immunization of people ≥ 65 years with an antigen concentration four times higher than the standard vaccine. Multiple clinical trials c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
5
0
2
Order By: Relevance
“…Whereas in Europe, B strains represent on average 20-25% of all circulating strains [12,13], in Spain, the circulation of B virus has reached 27.6% between 2000-2001 and 2015-2016 seasons [3,14]. Another recently published study has confirmed this result, showing that the median proportion of influenza B cases between 2007 and 2017 was 27.2% [15].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Whereas in Europe, B strains represent on average 20-25% of all circulating strains [12,13], in Spain, the circulation of B virus has reached 27.6% between 2000-2001 and 2015-2016 seasons [3,14]. Another recently published study has confirmed this result, showing that the median proportion of influenza B cases between 2007 and 2017 was 27.2% [15].…”
Section: Introductionmentioning
confidence: 89%
“…Other European countries have also recognized the value of QIV [20][21][22]. In Spain, between 2007 and 2017, when the WHO still recommended TIV [18], there has been a mismatch between the circulating B lineage and the one present in the vaccine, in four out of the ten seasons [15]. Overall, an estimated 53.9% of influenza B samples during this period were the influenza B strain not included in the vaccine [3].…”
Section: Introductionmentioning
confidence: 99%
“…116 Clinical trials have demonstrated that these VLPs are safe, tolerable, and induce a potent immune response. 117 Sanofi Pasteur, known as the largest producer of IVs worldwide, adapted the baculovirus-insect cells ES to produce the FluBlok flu vaccine. It is a recombinant seasonal influenza HA vaccine produced in Lepidopteran cell culture.…”
Section: Virus-like Particles Against Human Pappillomavirusesmentioning
confidence: 99%
“…Asimismo, con respecto a las enfermedades crónicas respiratorias, la vacunación reduce el número de sobreinfecciones bacterianas y contribuye a la reducción del número de hospitalizaciones y a la disminución del riesgo de muerte [43][44][45]. edad avanzada con respecto a las vacunas de dosis estándar [57][58][59] Existe pues una amplia evidencia científica que corrobora la idoneidad de estas vacunas en este colectivo, basada en la consistencia y robustez de los datos obtenidos en los múltiples estudios a lo largo de diferentes temporadas de gripe [56,58].…”
Section: Impacto Clínico De Las Bajas Coberturas Vacunalesunclassified
“…El empleo de vacunas más inmunógenas y efectivas que generen una mayor protección frente a las cepas circulantes, y con un perfil de seguridad adecuado, garantizarían una mejor cobertura vacunal en esta población. De hecho, diver-sos estudios han demostrado que la vacuna inactivada de virus fraccionados de alta dosis es una alternativa más inmunogénica y eficaz en la prevención de la infección por el virus de la gripe y sus complicaciones asociadas en la población de edad avanzada con respecto a las vacunas de dosis estándar [ 57 - 59 ] Existe pues una amplia evidencia científica que corrobora la idoneidad de estas vacunas en este colectivo, basada en la consistencia y robustez de los datos obtenidos en los múltiples estudios a lo largo de diferentes temporadas de gripe [ 56 , 58 ].…”
Section: Análisis Del Grupo De Expertosunclassified